Non-oral manifestations in adults with a clinical and molecularly confirmed diagnosis of periodontal Ehlers-Danlos syndrome - Angwin, C.; Zschocke, J.; Kammin, T.; Björck, E.; Bowen, J.; Brady, A. F.; Burns, H.; Cummings, C.; Gardner, R.; Ghali, N.; Gröbner, R.; Harris, J.; et al. (Frontiers in Genetics, 2023)
Periodontal Ehlers-Danlos Syndrome (pEDS) is a rare autosomal dominant type of EDS characterised by severe early-onset periodontitis, lack of attached gingiva, pretibial plaques, joint hypermobility and skin hyperextensibility as per the 2017 International EDS Classification. In 2016, deleterious pathogenic heterozygous variants were identified in C1R and C1S, which encode components of the complement system. Materials and Methods Individuals with a clinical suspicion of pEDS were clinically and molecularly assessed through the National EDS Service in London and Sheffield and in genetic services in Austria, Sweden and Australia. Transmission electron microscopy and fibroblast studies were performed in a small subset of patients. Results A total of 21 adults from 12 families were clinically and molecularly diagnosed with pEDS, with C1R variants in all families. The age at molecular diagnosis ranged from 21 – 73 years (mean 45 years), male: female ratio 5:16. Features of easy bruising (90%), pretibial plaques (81%), skin fragility (71%), joint hypermobility (24%) and vocal changes (38%) were identified as well as leukodystrophy in 89% of those imaged. Discussion This cohort highlights the clinical features of pEDS in adults and contributes several important additional clinical features as well as novel deleterious variants to current knowledge. Hypothetical pathogenic mechanisms which may help to progress understanding and management of pEDS are also discussed.